Stories for history in 1 degrees de abril - Franco Junior, Arnaldo [UNESP] (Univ Estadual Paulista-unesp, 2020)
1 degrees de abril - Estorias para a Historia, by Mario Lago, written and published in 1964 after the arbitrary arrest of the author, is one of the first literary records of the violence of the civil-military dictatorship established in Brazil in the second half of the 20th century. This paper analyzes the narrative plot of the first edition of the book, focusing on the relationships between the narrated stories and the record of historical facts.
Keywords: Dictatorship; History; Hybrid narrative; Mario Lago; Testimony